Studying the effect of quantum dots and parity-time symmetry on the magnification of topological edge state peak as a pressure sensor - Ameen, Ayman A.; Al-Dossari, M.; Zaky, Zaky A.; Aly, Arafa H. (Synthetic Metals, 2023)
In this paper, a novel pressure sensor employing parity-time symmetry for amplifying the sensing signal is proposed. The sensor design consists of a multi-layer dual–ternary photonic crystal with quantum dots embedded inside silicon dioxide and porous silicon layers as the unit cell of the structure. A topological edge state peak appears inside the photonic bandgap due to the sensor's symmetric design. The properties of the topological edge state peak are changing due to the photoelastic effect of the selected materials. Quantitive analysis of the sensor performance was conducted to optimize the periodicity number and the incidence angle. Moreover, the influence of silicon porosity and macroscopic Lorentz oscillation on the performance was examined.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Magnification; Parity-Time Symmetry; Porous Silicon; Pressure Sensor; Symmetric Photonic Crystal; Topological Edge State